Speaking out: Testimonial narratives of Chinese cyberpetitioners under networked authoritarianism. (December 2016) - Huang, Vincent Guangsheng
Abstract: In the digital age, virtual testimonies are an emerging socioliterary genre in which grievances are aired with the goal of inducing readers to participate in the project of social justice. Previous studies have provided insight into virtual testimonies in democratic contexts. This study contributes to the literature by exploring the features of virtual testimonies in democratically restricted environments and showing how such testimonial narratives both challenge and are shaped by networked authoritarianism. Taking a "testimonial narrative" approach, critical narrative analysis is used to analyze virtual testimonies published by 59 cyberpetitioners on blogs or microblogs on the Chinese Internet. These speaking subjects are found to transform the Internet׳s digital networks into narrative networks by constructing virtual testimonies. To evade censorship, they structure their plots and characters according to a central-local binary opposition that allows them to criticize local government authority without compromising their expression of loyalty to the central government. These narrators are also shown to use the narrative strategy of creatively appropriating the "official rhetoric" to construct and occupy the subject positions of "citizens" and "the people, " thereby justifying their cyberpetitioning activities. Beyond the Chinese context, this paper has wider implications for sociolinguistics of surveillance, narrative, ICT and social activism research. Highlights: This study identifies the "virtual testimony" as a common genre in which cyberpetitioners narrate traumatic experiences. Taking a "testimonial narrative" approach, critical narrative analysis is used to analyze these virtual testimonies. The analysis explores how such testimonial narratives both challenge and are shaped by online power dynamics.